PERAN RUMAH SINGGAH SAHABAT ANAK PUSPITA DALAM PENGEMBANGAN KOMUNIKASI SOSIAL ANAK-ANAK DI KAMPUNG TEGAL AMBA, DUREN SAWIT, JAKARTA TIMUR - Sinambela, Lasria; Maida, Serepina Tiur; Sarwoko, Tri Adi; wulandari, Silva Aresta; Tumanggor, Ojakma Sihar Panaili; Mantero, Emanuel; Hutagaol, Kerlima (LP2M STP Mataram, 2024)
The problems of children are difficult and endless and the presence of Rumah Singgah Sahabat Anak Puspita as a model of coaching and embracing children in the Tegal Amba Duren Sawit village area through education, skills training, moral education and tolerance. Different backgrounds are children in promiscuity, drugs, free sex, gambling, drinking. The emergence of Rumah Singgah Sahabat Anak Puspita is a place to encourage these children to get the right to a decent life, protection and can display positive behavior with norms and ethics in the community. The aim is to determine the benefits of the role of Rumah Singgah Sahabat Anak Puspita on Tegal Amba Village Children in Duren Sawit, East Jakarta. The method used is a participatory approach, with direct observation and in-depth interviews with children and shelter managers. The results show that the halfway house plays an important role in improving children's communication skills and social interactions, as well as creating an environment that supports their social development. Suggestions include building partnerships with other halfway houses in activity programs and involving the government to support activities